2016
DOI: 10.15403/jgld.2014.1121.252.pcr
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer: Multicenter Prospective Data Collection and Analysis by the Hungarian Pancreatic Study Group

Abstract: Background & Aims: Pancreatic cancer is a devastating disease with poor prognosis. There is very limited information available regarding the epidemiology and treatment strategies of pancreatic cancer in Central Europe. The purpose of the study was to prospectively collect and analyze data of pancreatic cancer in the Hungarian population. Methods: The Hungarian Pancreatic Study Group (HPSG) organized prospective, uniform data collection. Altogether 354 patients were enrolled from 14 Hungarian centers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
0
21
1
1
Order By: Relevance
“…Overall, ever smoking was associated with a significant 20% increase risk of death compared to never smoking (n=5 studies [88,89,93,94,96], HR 1.20, 95% CI 1.05, 1.37) with similar findings observed for current smokers compared to never smokers (n=5 studies [90][91][92]95,96], HR 1.19, 95% CI 0.97, 1.46), albeit non-significant. Former smokers experienced a 14% significant increase in mortality risk compared to never smokers (n=5 studies [90][91][92]95,96], HR 1.14, 95% CI 1.01, 1.30) and a marked worse survival was demonstrated in patients who recently quit smoking in the 15 years preceding cancer diagnosis (n=2 studies [92,96], HR 1.42 95% CI 1.16, 1.74).…”
Section: Pancreatic Cancer Smoking and Survival In Pancreatic Cancer mentioning
confidence: 59%
See 1 more Smart Citation
“…Overall, ever smoking was associated with a significant 20% increase risk of death compared to never smoking (n=5 studies [88,89,93,94,96], HR 1.20, 95% CI 1.05, 1.37) with similar findings observed for current smokers compared to never smokers (n=5 studies [90][91][92]95,96], HR 1.19, 95% CI 0.97, 1.46), albeit non-significant. Former smokers experienced a 14% significant increase in mortality risk compared to never smokers (n=5 studies [90][91][92]95,96], HR 1.14, 95% CI 1.01, 1.30) and a marked worse survival was demonstrated in patients who recently quit smoking in the 15 years preceding cancer diagnosis (n=2 studies [92,96], HR 1.42 95% CI 1.16, 1.74).…”
Section: Pancreatic Cancer Smoking and Survival In Pancreatic Cancer mentioning
confidence: 59%
“…We identified nine studies with available risk estimates for inclusion in the review [88][89][90][91][92][93][94][95][96] ( Supplementary table 4). Most studies were conducted in the United States.…”
Section: Pancreatic Cancer Smoking and Survival In Pancreatic Cancer mentioning
confidence: 99%
“…Our results are not comparable with international reports. Risch et al (USA group) [ 20 ], Lakatos et al (Hungarian group) [ 21 ], and Ruiz-Tovar et al (Spanish group) [ 21 ] reported 44.7% (42.8%–46.6%) of female patients, with variable mean ages of 68.5 years, 65.2 years and 63.7 years, respectively [ 22 ]. Our cohort presented a higher prevalence of PDAC in females and a slightly younger mean age than other studies ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable with a study by Risch et al that found that 69% of patients were smokers and 24.8% were obese with a mean BMI of 27 [ 20 ]. Lakatos et al identified that 28.5% of patients were smokers and 42.3% were overweight or obese [ 21 ], and Ruiz-Tovar found that 37.3% of patients were smokers and 3.4% were obese [ 22 ]. We only identified 28% of patients with type 2 diabetes mellitus, a well-known risk factor for PDAC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, not only are 60–70 million people affected by such diseases each year, but they also cause around a quarter million deaths annually and generate an estimated cost of $150 billion per year [ 7 ]. There is no specific therapy for many of these diseases, including pancreatitis and pancreatic cancer [ 10 12 ]. Of course, first, the pathomechanisms of the disease should be understood, new therapeutic targets revealed and the biomedical industry attracted [ 13 16 ].…”
Section: Discussionmentioning
confidence: 99%